Rad51 Interacts with Non-structural 3 Protein of Hepatitis C Virus and Regulates Viral Production - Son, Kidong; Nguyen, Tram T. T.; Choi, Jae-Woong; Pham, Long V.; Luong, Trang T. D.; Lim, Yun-Sook; Hwang, Soon B. (Frontiers in Microbiology, 2017)
Hepatitis C virus (HCV) is a leading cause of chronic liver disease affecting over 170 million people worldwide. Chronic infection with HCV progresses to liver fibrosis, cirrhosis, and hepatocellular carcinoma. HCV exploits host cellular factors for viral propagation. To investigate the cellular factors required for HCV propagation, we screened a siRNA library targeting human cell cycle genes using cell culture grown HCV-infected cells. In the present study, we selected and characterized a gene encoding Rad51. Rad51, a member of a conserved recombinase family, is an essential factor for homologous recombination and repair of double-strand DNA breaks. We demonstrated that siRNA-mediated knockdown of Rad51 significantly inhibited HCV propagation without affecting HCV RNA replication. Silencing of Rad51 impaired secretion of infectious HCV particles and thus intracellular viruses were accumulated. We showed that HCV NS3 specifically interacted with Rad51 and accumulated Rad51 in the cytosol. Furthermore, Rad51 was coprecipitated with NS3 and HCV RNA. By employing membrane flotation and protease protection assays, we also demonstrated that Rad51 was co-fractionated with HCV NS3 on the lipid raft. These data indicate that Rad51 may be a component of the HCV RNA replication complex. Collectively, these data suggest that HCV may exploit cellular Rad51 to promote viral propagation and thus Rad51 may be a potential therapeutic target for HCV.